2008
DOI: 10.1200/jco.2007.15.0235
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Chemotherapy: Updates of National Surgical Adjuvant Breast and Bowel Project Protocols B-18 and B-27

Abstract: B-18 and B-27 demonstrate that preoperative therapy is equivalent to adjuvant therapy. B-27 also showed that the addition of preoperative taxanes to AC improves response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

42
1,170
6
57

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,593 publications
(1,311 citation statements)
references
References 37 publications
42
1,170
6
57
Order By: Relevance
“…An alternative and more rapid approach is to evaluate the predictive value of a prognostic marker for chemosensitivity in the neoadjuvant setting. Here, the pathological response can be used as endpoint, since the achievement of pCR has gained wide acceptance as a predictor of a good long-term prognosis [20,21]. In this report a series of 167 patients with stage II and III primary invasive breast cancer who received neoadjuvant chemotherapy is described.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative and more rapid approach is to evaluate the predictive value of a prognostic marker for chemosensitivity in the neoadjuvant setting. Here, the pathological response can be used as endpoint, since the achievement of pCR has gained wide acceptance as a predictor of a good long-term prognosis [20,21]. In this report a series of 167 patients with stage II and III primary invasive breast cancer who received neoadjuvant chemotherapy is described.…”
Section: Discussionmentioning
confidence: 99%
“…12,17 The National Surgical Adjuvant Breast and Bowel Project (NSABP) B-18 trial demonstrated that, in a population with predominantly T2 disease ( 60%), neoadjuvant chemotherapy-associated tumor shrinkage altered the BC surgical intervention from a 60%/40% lumpectomy/mastectomy ratio after adjuvant chemotherapy to a 68%/32% lumpectomy/mastectomy ratio. 13 More recently, in a group of patients with mostly T3/T4 disease (80%), those with HER2-positive disease who received a neoadjuvant trastuzumab-based regimen exhibited a mean decrease in tumor size from 7.75 cm at baseline to 2.20 cm after neoadjuvant therapy, resulting in a 43.7% lumpectomy rate (unpublished data). In addition to treating detectable disease before surgery, neoadjuvant chemotherapy provides the earliest chance to treat micrometastatic disease, saving time that potentially could be lost to local treatment.…”
Section: Neoadjuvant Chemotherapy For the Treatment Of Breast Cancermentioning
confidence: 98%
“…In addition, among patients who were event-free for 5 years, regardless of age, DFS was greater in patients who received neoadjuvant therapy compared with the postoperative therapy group (HR, 0.81; P ¼ .053). 13 One important caveat with neoadjuvant chemotherapy, however, has been raised by a meta-analysis that compared the outcomes of neoadjuvant versus adjuvant treatment in BC. That analysis demonstrated an increase in locoregional failure for patients who had received neoadjuvant therapy if they subsequently did not undergo surgery and, instead, received radiotherapy.…”
Section: Neoadjuvant Chemotherapy For the Treatment Of Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…During NAC the treatment response may be monitored in vivo to obtain individualized treatment, i.e., by modifying ineffective treatments. The response to breast cancer chemotherapy has been shown to correlate with long-term outcome, although only complete pathologic response (pCR) has a major impact on disease free survival (DFS) and overall survival (OS) (2). Although pCR is the gold standard and associated with improved DFS and OS, there is also evidence for improved outcomes for clinical responders (3).…”
mentioning
confidence: 99%